2017
DOI: 10.2147/opth.s123640
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences of planning stereotactic radiosurgery using 3D printed models of eyes with uveal melanomas

Abstract: ObjectiveThe objective of this study was to determine the use of 3D printed model of an eye with intraocular tumor for linear accelerator-based stereotactic radiosurgery.MethodsThe software for segmentation (3D Slicer) created virtual 3D model of eye globe with tumorous mass based on tissue density from computed tomography and magnetic resonance imaging data. A virtual model was then processed in the slicing software (Simplify3D®) and printed on 3D printer using fused deposition modeling technology. The materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…6 3D printing was also used in surgical planning for orbital fracture repair 7 and in stereotactic surgery for uveal melanomas. 8 Other uses include the manufacturing of ocular prostheses 9 as well as various surgical instruments. 10 This is the first report in which a 3D printer was not only used for the creation of surgical and educational tools but was used in itself as a tool to foster innovation and creativity in an academic ophthalmic educational program.…”
Section: Discussionmentioning
confidence: 99%
“…6 3D printing was also used in surgical planning for orbital fracture repair 7 and in stereotactic surgery for uveal melanomas. 8 Other uses include the manufacturing of ocular prostheses 9 as well as various surgical instruments. 10 This is the first report in which a 3D printer was not only used for the creation of surgical and educational tools but was used in itself as a tool to foster innovation and creativity in an academic ophthalmic educational program.…”
Section: Discussionmentioning
confidence: 99%
“…Obtained patient observations confirmed that stereotactic irradiation for uveal melanoma using LINAC is feasible and well tolerated. This treatment preserves the patient's eye globe and is offered in the case of moderate or unfavorably localized uveal melanomas [5].…”
Section: Discussionmentioning
confidence: 99%
“…We introduced the 3D printing technology into a process of planning stereotactic radiosurgery (SRS) in patients as a treatment of intraocular tumor-uveal melanoma [5,6].…”
Section: For Surgical Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…To preserve the eye globe is the main goal in conservative treatment. Secondary neovascular glaucoma as complication after LSRS is the most frequent reason for enucleation; it varies from 10 % to 20 % [22]. Single dose one-day session LSRS with 35.0 Gy is adequate to treat small and medium stage melanoma [21].…”
Section: Discussionmentioning
confidence: 99%